2017
DOI: 10.1038/ncomms14255
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of organic matter controls methylmercury formation in boreal lakes

Abstract: A detailed understanding of the formation of the potent neurotoxic methylmercury is needed to explain the large observed variability in methylmercury levels in aquatic systems. While it is known that organic matter interacts strongly with mercury, the role of organic matter composition in the formation of methylmercury in aquatic systems remains poorly understood. Here we show that phytoplankton-derived organic compounds enhance mercury methylation rates in boreal lake sediments through an overall increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
209
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 246 publications
(220 citation statements)
references
References 51 publications
10
209
1
Order By: Relevance
“…As for THg, MeHg revealed a good distribution on the funnel plot and no asymmetry ( z = 0.66, p = 0.51). Negative relationships were found for only 8% (7/85) of all cases for THg (Brigham et al, ; Fagnani et al, ; Noh et al, ; Porvari & Verta, ; Vidon et al, ) and 12% (7/59) for MeHg (Bravo et al, ; Brazeau et al, ; Guedron et al, ; Porvari & Verta, ; Riscassi et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As for THg, MeHg revealed a good distribution on the funnel plot and no asymmetry ( z = 0.66, p = 0.51). Negative relationships were found for only 8% (7/85) of all cases for THg (Brigham et al, ; Fagnani et al, ; Noh et al, ; Porvari & Verta, ; Vidon et al, ) and 12% (7/59) for MeHg (Bravo et al, ; Brazeau et al, ; Guedron et al, ; Porvari & Verta, ; Riscassi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The most likely explanation is that biological processes responsible for the production of 1 mole of MeHg do not necessarily result in a 1:1 change in DOC concentration, hence reducing the coupling with DOC. Moreover, the origin and molecular composition of OM are critical parameters to understand Hg methylation and accumulation in lakes and rivers (Bravo et al, , ). Although Hall et al () found no significant relationship with DOC for MeHg, they did find significant relationships with HPOA and SUVA 254 , confirming the importance of the type and quality of DOC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations